Transcriptome and phytohormone analysis reveal mechanism of gall formation by Trichagalma acutissimae larvae on oak leaves - Wang, Yingnan; Xue, Chao; Wu, Saisai; Zhang, Yuanchen; Li, Ran; Li, Yujian; Yi, Xianfeng (Frontiers in Plant Science, 2025)
IntroductionGall formation caused by plant-organism interactions affects plant development and is essential for the life cycle of gall-inducing insects. Plant hormones like auxins and cytokinins, regulate gall development and defense responses. Despite the extensive morphological characterization of galls, the molecular mechanisms underlying gall induction remain largely unresolved.MethodsIn this study, we quantified hormone concentrations and performed transcriptome analyses to investigate the mechanisms by which leaf galls are induced by the cynipid wasp Trichagalma acutissimae on two oak host species, Quercus variabilis and Q. acutissima.ResultsOur preliminary results indicate that wasp larvae may synthesize auxins and cytokinins—a conclusion supported by the gall transcriptome data. Downregulation of IAA biosynthesis genes in gall tissues coincides with significantly higher IAA levels in the larvae compared to the leaves and galls. Likewise, the detection of active cytokinins in the larvae indicates their ability to synthesize cytokinins autonomously. Furthermore, we observed significant suppression of jasmonic acid (JA) biosynthesis in the gall tissues, which strongly supports the nutritional hypothesis. We also identified the upregulation of biosynthetic genes involved in carbohydrate metabolism, amino acid metabolism, and lipid metabolism, providing evidence for the ‘nutritional hypothesis’ of gall formation.DiscussionThis integrative exploration of hormonal dynamics and transcriptomic changes offers insights into the mechanisms of gall induction.